AN INVESTIGATION INTO TURKISH EFL LEARNERS' STEREOTYPED THOUGHTS AND EXPOSURE TO ENGLISH: A CORRELATIONAL STUDY - Hatice Okyar; Yusuf Demir (Informascope, 2019)
This study aims to investigate tertiary EFL learners' stereotyped thoughts about foreign languages, the extent of their exposure to English, and the potential relationships between these variables, also in relation to their proficiency level. 124 EFL students in the preparatory school of a state university in Turkey participated in the study. Two quantitative data collection instruments were distributed to the participants: Stereotyped Thoughts About Foreign Languages Scale (Ünal, 2015) and Exposure to English Scale (Gökcan & Çobanoğlu-Aktan, 2016). Descriptive statistics and correlations were used to analyze the data. The results showed that the participants held a moderate level of stereotyped thoughts and exposure to English. Moreover, significant and positive relationships were revealed between L2 exposure and (1) proficiency level and (2) the two dimensions of stereotyped thoughts: collectivity at a weak level and trying to change people at a moderate level. However, L2 exposure correlated significantly and negatively with taking it personally and exaggerated generalization at a weak level. Concerning the relationships between proficiency level and the dimensions of stereotyping, the "Must" rule, taking it personally and excessively self-sacrificing showed significant and negative relationships with proficiency level weakly, while exaggerated generalization correlated with proficiency at a moderate level. Keywords: L2 exposure, stereotypes, foreign languages, attitudes